Privatization of Credence Goods: Theory and an Application to Residential Youth Care - Erik Lindqvist (Research Institute of Industrial Economics (IFN), 2008)
A wide range of services provided by the public sector are credence goods, i.e., services for which the producer has private information whether a certain treatment is needed or not. This paper studies how ownership affects the incentives for producers to reveal such information to public procurers. I develop a model where procurers buy a more extensive treatment in case quality is high. Private firms have strong incentives to reduce cost and must be given rents in order not to shirk on non-contractible quality. The existence of rents makes private firms try to induce demand for unnecessary treatments. Public sector managers have no incentive to cut cost, implying that optimal contracts don't entail rents unless quality is very important. Public sector managers instead use their informational advantage to avoid unpleasant tasks. Empirical evidence from residential care for teenagers with behavioral problems supports the model's predictions. Private ownership prolongs the duration of treatment by more than a year, doubling total cost. Unlike private facilities, public facilities are much more likely to initiate treatment breakdowns for teenagers that are particularly burdensome to treat.
Keywords: H11; H40; L32; L33; 330; Privatization; Public Sector Contracting; Credence Goods; Incomplete Contracts; Contracting Out; Residential Youth Care; Juvenile Delinquency; Vertrauensgüter; Privatisierung; Dienstleistungssektor